Safety and efficacy of dry grape extract when used as flavouring in water for drinking for all animal species and categories. (2nd December 2016) - ,; Rychen, Guido; Aquilina, Gabriele; Azimonti, Giovanna; Bampidis, Vasileios; de Lourdes Bastos, Maria; Bories, Georges; Cocconcelli, Pier Sandro; Flachowsky, Gerhard; Gropp, Jürgen; Kolar, Boris; Kouba, Maryline; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of dry grape extract when added to water for drinking for all animal species and categories. The additive under assessment (dry grape extract) is a mixture of two extracts from the seeds and skin of Vitis vinifera subsp. vinifera . The FEEDAP Panel has previously issued an opinion on the safety and efficacy of this dry grape extract when added to feed. It was concluded that the additive is safe at the maximum proposed use level (100 mg/kg complete feed) for all animal species except dogs, for which no safe dietary concentration could be established. The FEEDAP Panel also concluded that there were no concerns for consumer safety and that no risks for the environment were to be expected and could not conclude on the safety for the user. Since consumer, user and environmental safety are independent of the mode of delivery of the additive, the conclusions reached in the previous opinion also apply to use in water. For a number of target species, the established safe concentration in feed could be exceeded if a maximum proposed dose in water (100 mg/L) was applied. Considering the margin of safety identified in the previous assessment, a maximum concentration of 50 mg/L water for drinking is considered safe for all animal species except dogs. Since the major component of the additive, the proanthocyanidin‐rich seed extract, is recognised to provide flavour in food and its function in water for drinking for animals would be essentially the same, no demonstration of efficacy is considered necessary.